1940 FDR, Willkie, Lindbergh, Hitler - the election amid the storm - Dunn, Susan 1945- (Yale Univ. Press, 2013)
The spellbinding story of the Roosevelt-Willkie election season, when bitterly divided Americans debated the fate of the nation and the world
Includes bibliographical references and index
Keywords: Roosevelt, Franklin D. / (Franklin Delano) / 1882-1945; Willkie, Wendell L. / (Wendell Lewis) / 1892-1944; Lindbergh, Charles A. / (Charles Augustus) / 1902-1974; Roosevelt, Franklin Delano / 1882-1945; Willkie, Wendell Lewis / 1892-1944; Lindbergh, Charles Augustus / 1902-1974; Willkie, Wendell L. -- 1892-1944; Lindbergh, Charles A. -- 1902-1974; Roosevelt, Franklin D. -- 1882-1945; USA -- Präsident; Geschichte 1900-2000; Geschichte 1940; Presidents / United States / Election / 1940; Isolationism / United States / History / 20th century; HISTORY / United States / 20th Century; BIOGRAPHY & AUTOBIOGRAPHY / Presidents & Heads of State; POLITICAL SCIENCE / Political Process / Elections; Geschichte; Politik; Präsidentenwahl; United States / Politics and government / 1933-1945; USA; Biografie